Traditional Exports and Trade Balance of Peru: An empirical approach - Cholan Ramos, Yoadis Elver; Rodríguez Abraham, Antonio Rafael (LACCEI, 2025)
This research evaluated the relationship of traditional exports and trade balance of Peru between 2019 and 2023. With a quantitative, applied and descriptive approach, and a non-experimental and longitudinal design, ex post facto data were analyzed using tables, graphs and correlational analysis. The results revealed a high positive relation (r = 0.764, p-value < 0.05) between traditional exports and the trade balance of Peru, suggesting that an increase in traditional exports significantly improves the trade balance. This finding underscores the importance of traditional exports as a key driver of Peru’s economic stability and growth.